Eugenio Martínez Celdrán, Análisis espectrográfico de los sonidos del habla. Ariel, Barcelona, 1998; 124 pp., figs. - Martín Butragueño, Pedro (El Colegio de México, 1999)
Se reseñó el libro: Análisis espectrográfico de los sonidos del habla.